Drop weight impact behaviour of sandwich panels with metallic micro lattice cores - Mines, R.A.W; Tsopanos, S.; Shen, Y.; Rafidah, Hasan; McKown, S.T. (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
The paper addresses the low velocity, drop weight behaviour of small (100 mm by 100 mm) sandwich panels with CFRP skins. The main point of interest is the core material, and the focus of the paper is in the use of body centred cubic (BCC) micro lattice cores made from Ti 6Al 4V titanium alloy and 316L stainless steel manufactured using selective laser melting. The mechanical behaviour of the micro lattice core is compared to that of conventional aluminium honeycomb. The paper discusses the manufacture and characterisation of the core materials, the measurement of core properties from strut tensile tests, block compression tests and the drop weight impact performance of the panels. Impact performance is expressed in terms of panel penetration. It is shown that the current Ti 6Al 4V BCC micro lattice cores are competitive with aluminium honeycomb, but that there is scope for improvement in Ti 6Al 4V micro strut mechanical properties. The SLM manufacturing process gives lattice structures with open cell architecture, which is an advantage for aerospace applications, and the SLM process can be used to realise a variety of cell lattice geometries.